Myrmecophilous rove beetles (Coleoptera: Staphylinidae) associated with Aenictus hodgsoni (Hymenoptera: Formicidae) from Thailand, with description of two new genera and three new species - Maruyama, Munetoshi; Komatsu, Takashi; Katayama, Yuji; Song, Xiao-Bin; Sakchoowong, Watana (Zootaxa, 2014)
Three species of rove beetles (subfamily Aleocharinae) were collected from colonies of Aenictus hodgsoni Forel, 1901 in Khao Yai National Park, Thailand. They are classified into three genera, including two new genera, and described herein as: Aenictobia siamensis Maruyama, sp. n. (tribe Aenictoteratini), Aenictosymbia cornuta Maruyama, gen. & sp. n. (tribe Lomechusini) and Aenictoxenides mirabilis Maruyama, gen. & sp. n. (tribe Pygostenini). The systematic positions of the new genera are discussed.